2020
DOI: 10.1016/j.envpol.2019.113606
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic fibers transfer from the water to the internal fluid of the sea cucumber Apostichopus japonicus

Abstract: Microplastics (MPs) are small plastic particles less than 5 mm in diameter. MPs in the form of microfibers (MFs) are widely detected in aquatic habitats and are of high environmental concern. Despite many reports on the effects of MFs on marine animals, their effect on sea cucumbers is still unclear. In addition, our previous filed study has shown that MFs may transfer to the coelomic fluid of the sea cucumber Apostichopus japonicus (A. japonicus). Here, we show how MFs transfer to the coelomic fluid of the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 63 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…The dominant type of plastic debris contained in this sample, accompanied by bre, fragments and lm. In the digestive organs of sea cucumbers, the type of microplastic that is easily transported by waves and reaches the digestive tract accumulates, resulting in digestive tract blockages from the absorption of plastic utensils known as bre (Taylor et al, 2016;Mohsen et al, 2020;Sayogo et al, 2019;Iwalaye et al, 2020). Besides, the abundance of bre was possibly attributed to the common usage of shing equipment, as plastic bres were important raw materials for shing nets and lines (Zhao et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The dominant type of plastic debris contained in this sample, accompanied by bre, fragments and lm. In the digestive organs of sea cucumbers, the type of microplastic that is easily transported by waves and reaches the digestive tract accumulates, resulting in digestive tract blockages from the absorption of plastic utensils known as bre (Taylor et al, 2016;Mohsen et al, 2020;Sayogo et al, 2019;Iwalaye et al, 2020). Besides, the abundance of bre was possibly attributed to the common usage of shing equipment, as plastic bres were important raw materials for shing nets and lines (Zhao et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, the concentration chosen for the present study is still higher than the concentrations reported from nature that are in the range of 1-10 fibers/L [17,23,24]. Yet, microplastic fiber concentrations used for exposure studies must be a compromise between environmental observations and concentrations that can be maintained as a reproducible and homogenous dispersion of fibers in the water column under laboratory conditions [20]. Furthermore, concentrations of microplastic fibers above currently reported levels can occur in local fiber contamination events, which might become more frequent in the future with rising plastic pollution [25].…”
Section: Introductionmentioning
confidence: 95%
“…In laboratory exposure studies, microplastic fibers tend to aggregate, settle to the bottom and adhere to the exposure vessels, and very little fibers stay suspended in the water column at low concentrations [20]. These difficulties often lead to the use of high concentrations of microplastics in exposure studies.…”
Section: Experimental Handling Of Microplastic Fibers In the Labmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of work to date has been on sea cucumbers. Individuals collected from the wild and experimental conspecifics were shown to ingest MNPs as they fed on sediments [132][133][134], with some studies showing translocation from the gut to the coelomic fluid. Ingestion rates were also found to correlate to water temperature [133] and therefore rising sea surface temperatures may result in increased dietary exposure.…”
Section: Association and Impact On Coral Reef Biotamentioning
confidence: 99%